Edukasi Perubahan Psikologis pada Ibu Menyusui di Wilayah Kerja Puskesmas Jongaya Kota Makassar - Haryati Sahrir; Karnely Karnely; Ni Luh Gede Sri Wahyudiantri; Nurmala Kamal (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
The World Health Organization (WHO) recommendation that mothers breastfeed for a minimum of 6 months has not been achieved, this is because the psychological condition of mothers after giving birth often experiences disturbances, which will affect breast milk production. This problem can occur due to the transition period to becoming a parent, the anxiety felt during post partum can be one of the factors influencing breast milk production. The aim of this service is to This service activity is carried out with the aim of providing information about psychological adaptation in breastfeeding mothers and how to carry out this psychological adaptation to achieve optimization of the role as a mother at the Jongaya Community Health Center. The number of participants in this service activity was 15 people which was held on July 28 2023 at the Jongaya Community Health Center using the lecture and question and answer method as well as the sharing method. The results of this activity show changes in behavior in the form of successful adaptation, especially in psychological changes during breastfeeding.